1998
DOI: 10.1093/oxfordjournals.jbchem.a022136
|View full text |Cite
|
Sign up to set email alerts
|

Role of Tissue Inhibitor of Metalloproteinases-2 (TIMP-2) in Regulation of Pro-Gelatinase A Activation Catalyzed by Membrane-Type Matrix Metalloproteinase-1 (MT1-MMP) in Human Cancer Cells

Abstract: To clarify the regulatory mechanism of pro-gelatinase A (proGelA) activation at a cellular level, expression of gelatinase A (GelA), three MT-MMPs, and TIMP-2 was examined with 11 human cancer cell lines cultured in the presence and absence of stimulants. MT1-MMP mRNA was expressed in 8 cell lines, while MT2-MMP and MT3-MMP mRNAs were expressed in fewer cell lines. The cells with high proGelA activation strongly expressed MT1-MMP mRNA but not MT2-MMP and MT3-MMP mRNAs, suggesting that MT1-MMP was responsible f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 27 publications
3
71
0
1
Order By: Relevance
“…TIMP2 is reported to regulate matrix degradation, acting through a membrane type MMP (MT1-MMP; 55,56). MT1-MMP is a key enzyme in tumor angiogenesis and metastasis, hydrolyzes a variety of ECM components, and is a physiologic activator of pro-MMP2 (57).…”
Section: Discussionmentioning
confidence: 99%
“…TIMP2 is reported to regulate matrix degradation, acting through a membrane type MMP (MT1-MMP; 55,56). MT1-MMP is a key enzyme in tumor angiogenesis and metastasis, hydrolyzes a variety of ECM components, and is a physiologic activator of pro-MMP2 (57).…”
Section: Discussionmentioning
confidence: 99%
“…TIMP-2 can bind to proMMP-2 via C-terminal interaction, and to MT1-MMP by its N-terminal domain. This dual binding brings proMMP-2 close to cell surface, where it can be activated by neighboring TIMP-2-free MT1-MMP molecules (Shofuda et al, 1998;Butler et al, 1998). It has been reported that the entire propeptide domain of MT1-MMP is required for the TIMP-2 binding and subsequent proMMP-2 activation (Cao et al, 1998).…”
Section: Paradox 2: Timps Regulate Pro-mmp Activation and Tumor Angiomentioning
confidence: 99%
“…These contradictory facts promote one to investigate and rede®ne the net role of TIMPs on tumorigenesis. As summarized in Table 1 and Figure 1, in contrast to its well-established antitumor e ect, TIMP may also function in favor of tumor growth either in an MMP-independent or MMP-dependent manner, including (a) growth promotion and anti-apoptotic e ect (Hayakawa et al, 1992; Guedez et al, 1998;Li et al, 1999;Jiang et al, 2001); (b) inhibition of angiostatin and endostatin-converting MMPs or upregulation of VEGF (Yoshiji et al, 1998), and therefore stimulation of angiogenesis; and (c) involvement of activation of pro-MMP-2 (Shofuda et al, 1998;Butler et al, 1998). The net e ect of TIMP on tumorigenesis may depend on bioavailability of local amount of TIMPs in tumor microenvironment, the time when the TIMP is presented to the tumor cells, and the presence of putative TIMP receptor on tumor cells.…”
Section: Paradox 4: Association Of Poor Prognosis With Increased Timpmentioning
confidence: 99%
See 1 more Smart Citation
“…Human squamous cell carcinoma HSC-4 cells expressed endogenous MT1-MMP [18], and thereby induced the activation of MMP-2, which was stimulated by 3-D collagen culture, and was blocked by MMP inhibitor (BB94) treatment (Fig. 1A).…”
Section: Mt1-mmp Is Required For Proliferation Of Cancer Cells In 3-dmentioning
confidence: 99%